2010
DOI: 10.1073/pnas.1000589107
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors regulate GABA A receptor lateral mobility and clustering at inhibitory synapses through serine 327 on the γ2 subunit

Abstract: Modification of the number of GABA A receptors (GABA A Rs) clustered at inhibitory synapses can regulate inhibitory synapse strength with important implications for information processing and nervous system plasticity and pathology. Currently, however, the mechanisms that regulate the number of GABA A Rs at synapses remain poorly understood. By imaging superecliptic pHluorin tagged GABA A R subunits we show that synaptic GABA A R clusters are normally stable, but that increased neuronal activity upon glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
219
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(241 citation statements)
references
References 36 publications
21
219
1
Order By: Relevance
“…We found that QD-labeled GABA A Rs could be reversibly recruited to these clathrin-rich structures in which they displayed a reduced lateral mobility compared with receptors outside the EZ, suggesting that the receptors are being confined to these subdomains, before their endocytosis. This is similar to the confined behavior of GABA A Rs observed at the inhibitory postsynaptic site, with similar diffusion coefficient values for the mobility of the receptors previously recorded at the synapse to those observed at EZs (Bannai et al, 2009;Muir et al, 2010). This suggests that both inhibitory postsynaptic sites and EZs are specialized dendritic subdomains that share similar GABA A R confinement mechanisms via reversible interactions with submembranous synaptic or EZ proteins, such as gephyrin and AP2, respectively.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…We found that QD-labeled GABA A Rs could be reversibly recruited to these clathrin-rich structures in which they displayed a reduced lateral mobility compared with receptors outside the EZ, suggesting that the receptors are being confined to these subdomains, before their endocytosis. This is similar to the confined behavior of GABA A Rs observed at the inhibitory postsynaptic site, with similar diffusion coefficient values for the mobility of the receptors previously recorded at the synapse to those observed at EZs (Bannai et al, 2009;Muir et al, 2010). This suggests that both inhibitory postsynaptic sites and EZs are specialized dendritic subdomains that share similar GABA A R confinement mechanisms via reversible interactions with submembranous synaptic or EZ proteins, such as gephyrin and AP2, respectively.…”
Section: Discussionsupporting
confidence: 64%
“…SEP ␥2 (Superecliptic pHluorin) has been described previously (Muir et al, 2010). Untagged ␣1 was in pRK5 and was described previously (Twelvetrees et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HALO-FLU may regulate GABA-A receptor activity by altering the number of GABA-A receptors available to GABAergic ligands on the cell membrane, resulting in increased GABAergic transmission, GABA release, and compensatory downregulation of GABA-A receptors (Kumar et al 2005). There is evidence that GABAergic deficit in PFC of schizophrenia patients is accompanied by compensatory upregulation of GABA-A receptors (Wassef et al 2003), so downregulation of GABA-A receptors, induced by chronic HALO-FLU, might follow an increase in GABAergic activity, consistent with evidence of dynamic changes in GABA receptor localization (Muir et al 2010). …”
Section: Discussionmentioning
confidence: 59%